Link Backup Backhaul With Machine To Machine (M2M) Utilizing LTE 4G Networks Using Mikrotik Router - Bagaskara, Vinsensius Dona (INDONESIAN JOURNAL OF SUSTAINABILITY, 2024)
The system in the internet network is currently very much needed in information technology that is developing very rapidly and quickly. In this case, in order to increase extra services in making a network that can connect several networks into the real main network, this is called a backhaul network consisting of a core network and small subnetworks or what is called a backbone which is in the edge network. The need for backhaul links within this company spurred internet service providers or Internet Service Providers (ISP) to develop and build a backhaul network system that is safe and not mixed up with networks on the internet where this link will be direct. To build a backhaul network that functions as a Fiber Optic backhaul backup link, there is a breakthrough which can use Machine To Machine (M2M) media utilizing the 4G / LTE network with supporting devices Mikrotik Router that has been modified with an Internal LTE Dongle Modem in which router with a 4G / LTE Machine to Machine (M2M) link can become a Virtual backhaul that replaces a physically formed pipeline backhaul, the difference in this case is the form of the link and the supporting devices used in it. Keywords: Backhaul, Backbone, Internet Service Provider, LTE, Machine To Machine, Mikrotik.